What a waste – A norm-critical design study on how waste is understood and managed - Fagerholm, Anna Sara; Haller, Henrik; Warell, Anders; Hedvall, Per Olof (Resources, Conservation & Recycling Advances, 2023)
This article seeks to contribute new insights into inclusive recycling environments through universal design. The aim is to develop knowledge on how waste is understood and managed by exploring the practice and design of a recycling environment. Applying a norm-critical view, this is explored in a study with participants from a municipal housing company and waste management company in northern Sweden. Methods used are go-along interviews together with professionals and observations of a recycling environment. The results are discussed as: 1) the “(un)social norm;” where our results show that the waste system is perceived as a social system, contradicting previous approaches where waste systems are treated as technical environments. 2) the “(un)design factor;” where we identify how design in a recycling context that doesn´t emphasise diversity may affect activities of sorting.